2020
DOI: 10.3389/fonc.2020.591846
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of a Machine Learning Algorithm With Object Detection Within the Thyroid Imaging Reporting and Data System Improves the Diagnosis of Genetic Risk

Abstract: Background The role of next generation sequencing (NGS) for identifying high risk mutations in thyroid nodules following fine needle aspiration (FNA) biopsy continues to grow. However, ultrasound diagnosis even using the American College of Radiology’s Thyroid Imaging Reporting and Data System (TI-RADS) has limited ability to stratify genetic risk. The purpose of this study was to incorporate an artificial intelligence (AI) algorithm of thyroid ultrasound with object detection within the TI-RADS s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Nguyen et al extracted picture features from ultrasound thyroid images in two domains: the spatial domain using deep learning and the frequency domain using Fast Fourier transform and confirmed that the combination of AI and ultrasound imaging is beneficial for the detection of benign and malignant thyroid nodules (8). Wang et al used a device combining ultrasound and AI to identify 600 images of thyroid nodules with a sensitivity of 86.20% and a specificity of 85.48%, indicating that AI ultrasound plays a significant role in the clinical diagnosis of thyroid disease (9). Chi et al preprocessed ultrasound pictures of the thyroid to eliminate artifacts and then fine-tuned the preprocessed GoogleNet model to extract features.…”
Section: Intelligent Application Of Ultrasound Imaging To the Thyroidmentioning
confidence: 93%
“…Nguyen et al extracted picture features from ultrasound thyroid images in two domains: the spatial domain using deep learning and the frequency domain using Fast Fourier transform and confirmed that the combination of AI and ultrasound imaging is beneficial for the detection of benign and malignant thyroid nodules (8). Wang et al used a device combining ultrasound and AI to identify 600 images of thyroid nodules with a sensitivity of 86.20% and a specificity of 85.48%, indicating that AI ultrasound plays a significant role in the clinical diagnosis of thyroid disease (9). Chi et al preprocessed ultrasound pictures of the thyroid to eliminate artifacts and then fine-tuned the preprocessed GoogleNet model to extract features.…”
Section: Intelligent Application Of Ultrasound Imaging To the Thyroidmentioning
confidence: 93%
“…The search identified 166 studies from January 2012 to April 2022; of these, 63 were further considered. After a full text read, the final studies included in the review were 30 in number; they are all listed below in Table 1 [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…Authors have used a dataset of 12000 instances and it was observed that Ensemble II gives high accuracy over Ensemble I. In [15] authors have applied object detection model T1-RADS for identifying the genetic risk in thyroid disease.…”
Section: Literature Surveymentioning
confidence: 99%